Targeting FAK, VEGF, and MTA1 proteins with Terminalia elliptica: a computational approach for anticancer activity - Shreevatsa, Bhargav; Hegde, Shrivatsa; Narayan, Prakruthi; Dharmashekar, Chandan; Jain, Anisha; Wani, Tanveer A.; Prabhuswamimath, Samudyata C.; Kollur, Shiva Prasad; Shivamallu, Chandan (Frontiers in Oncology, 2024)
Cancer remains a significant global health challenge, prompting exploration into alternative treatments such as those derived from natural compounds found in traditional medicine. Recent research has underscored the role of proteins like Focal Adhesion Kinase (FAK), Vascular Endothelial Growth Factor (VEGF), and Metastasis-Associated Protein 1 (MTA1) in driving cancer cell proliferation and survival. Here, we investigated the potential of a single molecule to modulate these key proteins involved in metastasis, offering a promising avenue for cancer therapy. Terminalia elliptica, commonly known as Asna, possesses a diverse range of medicinal properties, including antimicrobial, anti-inflammatory, anticancer, antidiabetic, antiaging, hepatoprotective, antioxidant, and neuroprotective activities. Our study aimed to explore the anticancer potential of Terminalia elliptica by identifying bioactive compounds capable of targeting FAK, VEGF, and MTA1 to impede cancer metastasis. Through in silico analysis, we conducted network analysis using Cytoscape to assess the significance of these bioactive compounds in the inhibition of signaling pathways driving metastasis. The utilization of these bioactives as potential candidates for targeted therapy of VEGF, FAK, and MTA1 regulated pathways was preliminarily assessed by Molecular Docking and MD Simulation. Our findings revealed that phytobioactives namely, Chebulinic Acid of Terminalia elliptica, exhibited notable binding affinity and interaction with FAK, and Chebulagic Acid with VEGF, and MTA1. This discovery holds promise as a novel therapeutic approach for combating cancer, offering potential benefits in cancer treatment and management.